1993
DOI: 10.1007/bf01606542
|View full text |Cite
|
Sign up to set email alerts
|

Prostate specific antigen and prostate specific acid phosphatase in adenocarcinoma of Skene's paraurethral glands and ducts

Abstract: An autopsy case of adenocarcinoma of Skene's paraurethral gland co-incident with renal cell carcinoma is described. The adenocarcinoma showed distinct prostate specific antigen and prostate specific acid phosphatase pointing to the equivalence between the male prostate and Skene's paraurethral glands and ducts. Skene's gland are the homologue of the prostate in females and tumours arising from them are immunohistochemically similar to male prostate carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0
23

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 19 publications
2
40
0
23
Order By: Relevance
“…Development from adenocarcinomas primarily arising in the periurethral glands [13,15,20,21] with secondary clear cell transformation may also occur. Clear cell and common adenocarcinomas of the periurethral ducts in women have been reported to stain positively for prostate-specific acid phosphatase and prostate antigen, suggesting female paraurethral glands to be homologous to the prostate glands [20][21][22]. The herein presented carcinoma in a male patient did not show immunohistochemical positivity for the prostate markers, confirming the results of others [10].…”
Section: Discussionsupporting
confidence: 79%
“…Development from adenocarcinomas primarily arising in the periurethral glands [13,15,20,21] with secondary clear cell transformation may also occur. Clear cell and common adenocarcinomas of the periurethral ducts in women have been reported to stain positively for prostate-specific acid phosphatase and prostate antigen, suggesting female paraurethral glands to be homologous to the prostate glands [20][21][22]. The herein presented carcinoma in a male patient did not show immunohistochemical positivity for the prostate markers, confirming the results of others [10].…”
Section: Discussionsupporting
confidence: 79%
“…A recent study showed 66.7% PSA and PAP-positive cases among 33 studied [25]. However, the negativity of the PSA on tumor tissue does not necessarily deny this origin [8].…”
Section: Discussionmentioning
confidence: 91%
“…4,5,11,12 Some examples of such nonspecific staining have been seen in apocrine sweat gland tumors of the skin and breast, oncocytoma of the parotid gland, carcinomas of the pancreas, urinary bladder, ovary, and paraurethral glands, pleomorphic adenomas, Warthin's tumors, mucoepidermoid carcinomas, and adenoid cystic carcinomas of the salivary gland. [5][6][7][8][9][10][11][12] Certainly, the two male patients who presented in this study with malignant breast tumor and PSA positivity did create such a dilemma. Also, since in both cases, apart from breast mass, symptoms of on-and-off urinary incontinence were present.…”
Section: Discussionmentioning
confidence: 91%
“…2 Recently, the commonly held belief that immunostaining of PSA is specific for prostate epithelium has been questioned, due to its demonstration in nonprostatic tissues 4,5 and nonprostatic neoplasms. [5][6][7][8][9][10][11][12] Therefore, it seems reasonable to assume that expression of PSA is not restricted to the prostate gland, and its demonstration in other neoplasms cannot be considered as an unequivocal evidence of prostatic origin.…”
mentioning
confidence: 99%